(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Employee wellness programs are initiatives companies use to improve the health of their workers but aim to reduce health-related absenteeism and increase employee productivity. Wellness programs promote employee’s well-being. Bestlink College of the Philippines has different programs that help employees relieve stress at work because the hard work of the employees also reflects the image of Bestlink College of the Philippines. According to the study, the majority of respondents were female and between the ages of 31-40. The majority of them had 2-5 years in service, with 21 teaching personnel each. The majority of them were from the BSED department, and the majority of respondents were full- time teachers. It also reveals that the teaching personnel are satisfied with the wellness programs of the Bestlink College of the Philippines. At the end of the study, the researcher suggests maintaining the wellness of the employees for satisfaction. And retain talent by promoting more wellness programs like stress management programs, yoga sessions, and gym membership.